Lipofibromatous hamartoma of the median nerve: 3T MRI evaluation by constrained spherical deconvolution analysis. Issue 4 (August 2018) - Arrigo, Alessandro; Gaeta, Michele; Calamuneri, Alessandro; Mormina, Enricomaria; Marino, Silvia; Stagno d'Alcontres, Francesco; Longo, Marcello; Granata, Francesca
In this study we described a case of lipofibromatous hamartoma involving the median nerve. We adopted diffusion tensor imaging and constrained spherical deconvolution-based tractography to reconstruct the affected median nerve. Moreover, we extracted diffusion-based parameters reflecting axonal integrity loss of median nerve fibres. Our data showed that constrained spherical deconvolution-based tractography outperformed the diffusion tensor imaging-based method, allowing the detection of the entire median nerve, including its branches, thus offering a robust method to investigate the involvement of the median nerve in pathological conditions. All clinical and technical implications are extensively described.